2008
DOI: 10.1152/ajpregu.90403.2008
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation of ion regulatory capacities in gills of marine fish under environmental hypercapnia

Abstract: Deigweiher K, Koschnick N, Pö rtner H, Lucassen M. Acclimation of ion regulatory capacities in gills of marine fish under environmental hypercapnia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
98
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(110 citation statements)
references
References 48 publications
9
98
1
Order By: Relevance
“…Additionally, damselfish larvae reared at elevated pCO 2 (550 to 1030 ppm) exhibited up to an 18% increase in length-at-age, which the authors suggested could be accomplished either through in creased energy intake or decreased energy expenditure (Munday et al 2009). In a captive rearing environment, prey are consistently provided at higher quantities than what is expected in nature; thus, larvae in the present study may have been able to increase their energy intake to compensate, or overcompensate, for an in crease in the metabolic cost of acid -base balance under acidified conditions (Deigweiher et al 2008. This has been demonstrated with mussels in both laboratory and natural marine environments, where food availability predominantly influences growth compared to increased pCO 2 ).…”
Section: Swimming Activitymentioning
confidence: 49%
“…Additionally, damselfish larvae reared at elevated pCO 2 (550 to 1030 ppm) exhibited up to an 18% increase in length-at-age, which the authors suggested could be accomplished either through in creased energy intake or decreased energy expenditure (Munday et al 2009). In a captive rearing environment, prey are consistently provided at higher quantities than what is expected in nature; thus, larvae in the present study may have been able to increase their energy intake to compensate, or overcompensate, for an in crease in the metabolic cost of acid -base balance under acidified conditions (Deigweiher et al 2008. This has been demonstrated with mussels in both laboratory and natural marine environments, where food availability predominantly influences growth compared to increased pCO 2 ).…”
Section: Swimming Activitymentioning
confidence: 49%
“…Similar observation of a bi-phasic acclimation reaction of acid-base transporters to environmental hypercapnia were observed in teleosts, including Atlantic cod (Gadus morhua) 50 and eelpout (Zoarces viviparus). 122 However during prolonged acclimation to hypercapnic conditions, expression levels of acid-base relevant transporters returned back to control levels potentially shifting to an energetically favorable reorganization of physiological features to cope with moderate hypercapnic conditions over longer exposure times. Furthermore, this reorganization of physiological features, including a metabolic shift upon chronic exposure to hypercapnic conditions is essential in order to reduce extra-free radical stress and keep cellular metabolic and redox state in balance.…”
Section: Role Of Ion Regulatory Epithelia During Acclimation To Envirmentioning
confidence: 99%
“…This observation suggests that prolonged RBC shrinkage may have compromised membrane integrity resulting in atypically fragile cells, a phenomenon that has also been observed in lungfish (Koldkjaer et al, 2002). Regardless, it does appear that an NHE isoform may be operating on the sablefish RBC membrane to maintain pH and cell volume homeostasis, likely a 'housekeeping' NHE1 (Claiborne et al, 1999;Deigweiher et al, 2008); however, further studies are required to address this.…”
Section: Cell Volume Regulationmentioning
confidence: 99%